Hubungan Antara Paritas dengan Kejadian Ruptur Perineum (Literature Review) - Diana Khoirul Khafidloh; Eighty Mardiyan Kurniawati; Ivon Diah Wittiarika (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Perineal tears occurs either spontaneously with vaginal or instrument delivery, or as a result of an episiotomy. Severe perineal tears can involve damage to the anal sphincter and anal mucosa. Perineal tears is caused by several factors which are classified into three groups. Such as maternal factors, delivery procedures, and mothers where parity is a factor in perineal tears. This study used a literature review study design. Research article searches were sourced from the Pubmed, Google Scholar, SCOPUS, scientificdirect, and BMC electronic databases. Search articles using keywords, namely perineal tears, parity, obstetric sphincter anal injuries. The results of a review of nine journals that have been carried out show that parity with a small number can cause perineal tears with a high degree, and vice versa parity with a high number further reduces the degree of perineal tears. But it is also affected by physical activities such as gymnastics and sports which can help to reduce the risk of perineal tears regardless of existing parity. The data that we reviewed can be concluded that there is a relationship between parity and perineal tears.